Full and partial hydrolysis of poly(2-oxazoline)s and the subsequent post-polymerization modification of the resulting polyethylenimine (co)polymers. Issue 40 (25th September 2018) - Mees, Maarten A.; Hoogenboom, Richard
Abstract : This review discusses the full and partial hydrolysis of poly(2-oxazoline)s as well as the synthetic methods that have been reported to modify the resulting secondary amine groups. Abstract : The synthesis of linear polyethylenimine (L-PEI) is mostly performed via the acidic or basic hydrolysis of poly(2-alkyl-2-oxazoline)s (PAOx). Besides full hydrolysis leading to L-PEI, the partial hydrolysis of the PAOx sidechains results in PAOx-PEI copolymers having secondary amine groups in the polymer backbone. The secondary amine groups of L-PEI and PAOx-PEI can act as charge carriers for the complexation of DNA for gene therapy. Furthermore, they are also excellent chemical moieties for post-polymerization modification reactions providing straightforward access to new PAOx (co)polymers based on a variety of PAOx, including the commercially available poly(2-ethyl-2-oxazoline) (PEtOx). Within this review, we will discuss the acidic and basic (partial) hydrolysis of PAOx as well as the corresponding mechanisms. In addition, an overview of the recent literature on the post-polymerization modification of the fully hydrolyzed L-PEI and the partially hydrolyzed PAOx-PEI is provided.